2017
DOI: 10.1080/21505594.2017.1391446
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood vessels are a niche for blood-borne meningococci

Abstract: Neisseria meningitidis is the causative agent of cerebrospinal meningitis and that of a rapidly progressing fatal septic shock known as purpura fulminans. Meningococcemia is characterized by bacterial adhesion to human endothelial cells of the microvessels. Host specificity has hampered studies on the role of blood vessels colonization in N. meningitidis associated pathogenesis. In this work, using a humanized model of SCID mice allowing the study of bacterial adhesion to human cells in an in vivo context we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 39 publications
(67 reference statements)
1
36
0
1
Order By: Relevance
“…In this model, where vessels of human origin from the graft anastomose to the mice vessels, blood-borne N. meningitidis readily adhere to human endothelial cells. Bacterial-induced vascular damages are very similar to those described in patients, including perivascular infiltrates, thrombosis, and vascular leakage associated with massively infected vessels (Harrison et al, 2002) that ultimately lead to the death of infected grafted animals (Capel et al, 2017). In addition, vascular damages are localised only in vessels colonised by meningococci.…”
Section: The Importance Of Endothelial Cell Colonisation the Achilmentioning
confidence: 64%
See 3 more Smart Citations
“…In this model, where vessels of human origin from the graft anastomose to the mice vessels, blood-borne N. meningitidis readily adhere to human endothelial cells. Bacterial-induced vascular damages are very similar to those described in patients, including perivascular infiltrates, thrombosis, and vascular leakage associated with massively infected vessels (Harrison et al, 2002) that ultimately lead to the death of infected grafted animals (Capel et al, 2017). In addition, vascular damages are localised only in vessels colonised by meningococci.…”
Section: The Importance Of Endothelial Cell Colonisation the Achilmentioning
confidence: 64%
“…They reduce colonisation of the human vessels by circulating meningococci and prevent subsequent vascular dysfunctions, intravascular coagulation, and overwhelming inflammation, the hallmarks of invasive meningococcal infections. Finally, in consistence with the role of the vascular niche in promoting sustained bacteraemia leading to mice lethality (Capel et al, ), these compounds reduce bacteraemia and increase mice survival. In association with antibiotics, they reduce vascular inflammatory and thrombotic responses that were shown to be highly detrimental and correlated with the severity of the disease in patients (Girardin, Grau, Dayer, Roux‐Lombard, & Lambert, ; van Deuren et al, ; Waage, Brandtzaeg, Halstensen, Kierulf, & Espevik, ).…”
Section: Blood‐borne Colonisation Of the Vascular Compartmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Of most interest, this model also revealed that, in the absence of vascular colonisation, bacteraemia rapidly drops and mice survive to infection, whereas Tfp‐mediated colonisation is associated with sustained bacteraemia and mice lethality. Thus, Tfp‐mediated interaction with vascular wall provides a niche for bacterial replication and constitutes a decisive step in disease progression (Capel et al, ; Denis et al, ). Overall, these studies demonstrated the essential role of Tfp in meningococcal pathogenesis.…”
Section: Role Of Type IV Pili In Meningococcal Pathogenesismentioning
confidence: 99%